2018
DOI: 10.1021/acs.energyfuels.7b03887
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on In Situ Preparation of Supported Sorbent for Moderate Temperature CFB-FGD

Abstract: Supported sorbent for flue gas desulfurization was prepared by a process of hydrating and drying a mixture of carrier particles and lumps of CaO in previous studies. Supported sorbent achieves high desulfurization efficiency in a Circulating Fluidized Bed (CFB) reactor at moderate temperature. However, the preparation process is complicated, which makes industrial application difficult. In this study, supported sorbent is prepared in situ in a CFB reactor by a coating process, in combination with SO2 removal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…This causes the low utilization ratio of the sorbent. To improve both the desulfurization efficiency and the sorbent utilization, a supported sorbent was developed in our previous studies to adhere small sorbent particles to relatively large inert particles, as shown in Figure . Several bench-scale experiments along with numerical analysis have also been conducted to study the reaction mechanism. …”
Section: Introductionmentioning
confidence: 99%
“…This causes the low utilization ratio of the sorbent. To improve both the desulfurization efficiency and the sorbent utilization, a supported sorbent was developed in our previous studies to adhere small sorbent particles to relatively large inert particles, as shown in Figure . Several bench-scale experiments along with numerical analysis have also been conducted to study the reaction mechanism. …”
Section: Introductionmentioning
confidence: 99%